PERKEMBANGAN DAKWAH ISLAM DI IRAN - Iskandar Iskandar (KOMUNIDA : Media Komunikasi dan Dakwah, 2015)
The background process of the development of Islam in Iran initiated by the Caliph Umar bin Khattab in doing Expansion Islamic regions. 820 M. Persian practically the entire territory under the control of the full caliph in Baghdad. In the year 820 AD sprung too small dynasties and large in different regions of the Persian alternating control of the territories Persia. For example Tahiri Dynasty (820-872 AD) in Khurasan (Iran), Samanid Dynasty (892-999 AD), Gaznawi (999-1037 AD) and Saljuk (1037-1157 AD). Then came the Safavids (1501-1732 AD) through the movement of Shia congregation bermazhab. The Iranian Revolution is something monumental in the history of Iran, the most prominent of course is a major change in the political sphere, namely the system formed a new government called the Islamic Republic of Iran. Based on the new political system and independent, Iran then do a big leap in the other fields. Including education (science and technology).